Blenderized Enteral Nutrition Diet Study: Feasibility, Clinical, and Microbiome Outcomes of Providing Blenderized Feeds Through a Gastric Tube in a Medically Complex Pediatric Population. Issue 6 (16th January 2018) - Gallagher, Kelsey; Flint, Annika; Mouzaki, Marialena; Carpenter, Andrea; Haliburton, Beth; Bannister, Louise; Norgrove, Holly; Hoffman, Lisa; Mack, David; Stintzi, Alain; Marcon, Margaret
Abstract: Background: Chronically ill children often require feeding via gastrostomy tubes (G‐tubes). Commercial formula is most commonly used for enteral feeding; however, caregivers have been requesting blenderized tube feeds (BTFs) as an alternative. The objective of this study was to evaluate the feasibility of using BTFs in a medically complex pediatric population and assess their impact on clinical outcomes, as well as the microbiota. Methods: Twenty pediatric participants were included. Participants were G‐tube dependent and receiving ≥75% of their daily energy requirements from commercial formula. Over 4 weeks, participants were transitioned from commercial formula to BTF and were monitored for 6 months for changes in nutrient intake, gastrointestinal symptoms, oral feeding, medication use, and caregiver perceptions. Changes to intestinal microbiota were monitored by 16S rDNA‐based sequencing. Results: Transition onto BTF was feasible in 17 participants, and 1 participant transitioned to oral feeds. Participants required 50% more calories to maintain their body mass index while on BTFs compared with commercial formula. BTF micronutrient content was superior to commercial formula. Prevalence of vomiting and use of acid‐suppressive agents significantly decreased on BTFs. Stool consistency and frequency remained unchanged, while stool softener use increased. The bacterial diversity and richness in stool samples significantly increased, while the relative abundance of Proteobacteria decreased. Caregivers were more satisfied with BTFs and unanimously indicated they would recommend BTFs. Conclusion: Initiation and maintenance of BTFs is not only feasible in a medically complex pediatric population but can also be associated with improved clinical outcomes and increased intestinal bacterial diversity.